2019
DOI: 10.1634/theoncologist.2018-0563
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Blood Markers Identify Risk of Immune-Related Toxicity in Advanced Non-Small Cell Lung Cancer Treated with Immune-Checkpoint Inhibitors

Abstract: Background Immune‐checkpoint inhibitors (ICIs) are now standard of care for advanced non‐small cell lung cancer (NSCLC). Unfortunately, many patients experience immune‐related adverse events (irAEs), which are usually mild and reversible, but they require timely management and may be life threatening. No predictive markers of irAEs are available. Materials and Methods The neutrophil‐to‐lymphocyte ratio (NLR) and platelet‐to‐lymphocyte ratio (PLR) were evaluated in patients with NSCLC consecutively treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
164
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(194 citation statements)
references
References 39 publications
(56 reference statements)
10
164
4
Order By: Relevance
“…They also reported that the occurrence of any irAE was associated with a baseline NLR <3.0 and a baseline PLR <180 by univariate analyses. Multivariate modeling confirmed a baseline PLR <180 as the only independent predictive factor (19). These findings agree with the findings of the present study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…They also reported that the occurrence of any irAE was associated with a baseline NLR <3.0 and a baseline PLR <180 by univariate analyses. Multivariate modeling confirmed a baseline PLR <180 as the only independent predictive factor (19). These findings agree with the findings of the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Regarding the incidence of irAEs, a baseline PLR <156 was identified with multivariate logistic regression analysis as a significant risk factor (p=0.006). Pavan et al observed that a baseline PLR <180 was significantly associated with occurrence of any irAEs among non-small lung cancer patients (19). They also reported that the occurrence of any irAE was associated with a baseline NLR <3.0 and a baseline PLR <180 by univariate analyses.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, circulating biomarkers can be also applied for predicting toxicity in patients treated with ICIs [51, 52]. For instance, low baseline levels of NRL and PLR have been found associated with a higher risk for developing immune‐related adverse events from anti–PD‐1/PD‐L1 immunotherapy in NSCLC [53].…”
Section: Discussionmentioning
confidence: 99%
“…None of these biomarkers has been incorporated into clinical practice, but they may provide insight into irAE pathogenesis. For example, the association of neutrophil markers (CD177),35 neutrophil growth factors (G-CSF, GM-CSF),34 a high neutrophil:lymophocyte ratio,31 and high IL-6 and IL-17 levels3233 with high grade irAEs, particularly colitis, suggests there is an important role for Th17 adaptive immune responses and innate immunity, at least in ICI associated colitis. The association of B cell changes30 and baseline autoantibodies with irAE3637 suggests that humoral immunity may also play a role in some organ specific irAEs.…”
Section: Biomarkers Of Immune Related Adverse Eventsmentioning
confidence: 99%